(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
A documentary review was carried out on the production and publication of research papers related to the study of the variable EDUCATION AND DIGITAL ERA. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022 by Latin American institutions, achieving the identification of 218 publications. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors towards the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that Brazil with 76 publications was the Latin American country with the highest scientific production registered in the name of authors affiliated with institutions in that country. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material referring to the study of EDUCATION AND DIGITAL ERA in Latin America was Social Sciences with 109 published documents, and the Type of Publication most used during the period indicated above were Journal Articles with 69% of the total scientific production.